2021
DOI: 10.1017/neu.2021.25
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum BDNF, IL-1β, IL-6, TNF-α, CRP and leucocyte levels in unipolar mania and bipolar disorder

Abstract: Objective: Unipolar mania is not included in the DSM-5 as a separate diagnosis, although it is defined by widely accepted diagnostic criteria. The aim of this study was to investigate the differences between unipolar mania and bipolar disorder in terms of clinical and inflammatory parameters. Methods: The data of 495 hospitalized patients with bipolar disorder diagnoses were analyzed retrospectively. Forty met the diagnostic criteria for unipolar mania. Two patients refused to participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Twenty-one studies met the eligibility criteria and were included in the meta-analysis (Aghanwa, 2001 ; Akarsu et al, 2012 ; Amamou et al, 2018 ; Andrade-Nascimento, Miranda-Scippa, Nery-Fernandes, Kapczinski, & Quarantini, 2011 ; Angst, Gerber-Werder, Zuberbühler, & Gamma, 2004 ; Angst et al, 2019 ; Beesdo et al, 2009 ; Chang et al, 2022 ; Dakhlaoui, Essafi, & Haffani, 2008 ; Gorgulu, Uluturk, & Palabiyik, 2021 ; Grobler, Roos, & Bekker, 2014 ; Grover et al, 2021 ; Mittal, Mehta, Solanki, Swami, & Meena, 2013 ; Perugi et al, 2007 ; Rajkumar, 2016 ; Sangha et al, 2022 ; Sonkurt, Altınöz, Danışman Sonkurt, & Köşger, 2021 ; Stokes et al, 2020 ; Subramanian, Kattimani, Rajkumar, Bharadwaj, & Sarkar, 2016 ; Yazıcı & Çakır, 2012 ; Yazici et al, 2002 ). The flowchart with details on screening and study selection process is reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one studies met the eligibility criteria and were included in the meta-analysis (Aghanwa, 2001 ; Akarsu et al, 2012 ; Amamou et al, 2018 ; Andrade-Nascimento, Miranda-Scippa, Nery-Fernandes, Kapczinski, & Quarantini, 2011 ; Angst, Gerber-Werder, Zuberbühler, & Gamma, 2004 ; Angst et al, 2019 ; Beesdo et al, 2009 ; Chang et al, 2022 ; Dakhlaoui, Essafi, & Haffani, 2008 ; Gorgulu, Uluturk, & Palabiyik, 2021 ; Grobler, Roos, & Bekker, 2014 ; Grover et al, 2021 ; Mittal, Mehta, Solanki, Swami, & Meena, 2013 ; Perugi et al, 2007 ; Rajkumar, 2016 ; Sangha et al, 2022 ; Sonkurt, Altınöz, Danışman Sonkurt, & Köşger, 2021 ; Stokes et al, 2020 ; Subramanian, Kattimani, Rajkumar, Bharadwaj, & Sarkar, 2016 ; Yazıcı & Çakır, 2012 ; Yazici et al, 2002 ). The flowchart with details on screening and study selection process is reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of age comparability between UM and md-BD, 10 studies met the quality criterion (Akarsu et al, 2012 ; Beesdo et al, 2009 ; Chang et al, 2022 ; Gorgulu et al, 2021 ; Perugi et al, 2007 ; Rajkumar, 2016 ; Sangha et al, 2022 ; Sonkurt et al, 2021 ; Stokes et al, 2020 , UK cohort; Subramanian et al, 2016 ). On the contrary, illness duration comparability was warranted by the majority of studies, with just a few with unclear data (Grobler et al, 2014 ; Grover et al, 2021 ; Sangha et al, 2022 ; Yazıcı & Çakır, 2012 ) or a mean difference over 3 years between groups (Aghanwa, 2001 ; Andrade-Nascimento et al, 2011 ; Perugi et al, 2007 ; Sonkurt et al, 2021 ; Stokes et al, 2020 , France cohort).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown elevated levels of cytokines, such as TNF-α, interferon γ (IFN-γ), IL [ 12 ], complement cascade components [ 13 ], immunoglobulin [ 14 ], and inflammatory indicators such as CRP [ 15 , 16 ], in BD patients compared with healthy controls. Moreover, patients with unipolar mania showed higher serum levels of IL-6 and CRP than other patients with a BD diagnosis [ 17 ]. In this case, our patient showed increased levels of CRP, complement C3 and C4, and proinflammatory cytokines such as IFN-γ, IL-4, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…They seem to perform worse in visual memory and executive functions and show specific social cognition deficits (Sonkurt et al, 2022). Moreover, based on the evidence that bipolar spectrum disorders might be associated with specific peripheral biomarkers (e.g., Bartoli et al, 2022;Carvalho et al, 2020), a distinct inflammatory status was hypothesized in people with UM, characterized by higher serum levels of interleukin 6 and C-reactive protein (Gorgulu et al, 2021).…”
mentioning
confidence: 99%